Meningkatkan Kesejahteraan Masyarakat Melalui Layanan Informasi Terseleksi Perpustakaan Desa dengan Participatory Rural Appraisal (PRA) - Indriyanti, Maretha; Ahwan, Muh Ahlis (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2021)
Purpose. This study aims to show that selected information services (information dissemination) of village libraries can improve the prosperity of residents in the Wonosalam District Demak Regency.Methodology. the approach used in this study is Participatory Rural Appraisal (PRA), an action of three stages (preparation, implementation, and evaluation). PRA was carried out collaboratively by the village library, sub-district officials, and cadres of PKK (a group of women concerned about family well-being) in a frame of community service activity.Discussion. This study shows that there is potential for PKK-assisted residents to develop their talents and interests through selected information services from the village library. The PKK assisted residents and librarians carried out this activity to access and find appropriate sources of information from various media and train new entrepreneurship skills. This collaborative activity turned out to grow the residents of Wonosalam District, Demak Regency's skills and create an entrepreneurship view for their prosperity.Conclusion. the selected information service has made PKK assisted residents aware that the village library can open new information and insights and create user experiences for their lives. It gradually changes the residents' mindset and makes their families and surrounding communities able to be prosperous.